The clinicopathologic characteristics and prognostic significance of triple-negativity in node-negative breast cancer - Han Wonshik; Im Seock-Ah; Kim Jee; Oh Do-Youn; Han Sae-Won; Rhee Jiyoung; Ae Park In; Noh Dong-Young; Bang Yung-Jue; Kim Tae-You (BMC Cancer, 2008)
Abstract Background Triple-negative (TN) breast cancer, which is defined as being negative for the estrogen receptor (ER), the progesterone receptor (PR), and the human epidermal growth factor receptor 2 (HER-2), represents a subset of breast cancer with different biologic behaviour. We investigated the clinicopathologic characteristics and prognostic indicators of lymph node-negative TN breast cancer. Methods Medical records were reviewed from patients with node-negative breast cancer who underwent curative surgery at Seoul National University Hospital between Jan. 2000 and Jun. 2003. Clinicopathologic variables and clinical outcomes were evaluated. Results Among 683 patients included, 136 had TN breast cancer and 529 had non-TN breast cancer. TN breast cancer correlated with younger age (< 35 y, p = 0.003), and higher histologic and nuclear grade (p < 0.001). It also correlated with a molecular profile associated with biological aggressiveness: negative for bcl-2 expression (p < 0.001), positive for the epidermal growth factor receptor (p = 0.003), and a high level of p53 (p < 0.001) and Ki67 expression (p < 0.00). The relapse rates during the follow-up period (median, 56.8 months) were 14.7% for TN breast cancer and 6.6% for non-TN breast cancer (p = 0.004). Relapse free survival (RFS) was significantly shorter among patients with TN breast cancer compared with those with non-TN breast cancer (4-year RFS rate 85.5% vs. 94.2%, respectively; p = 0.001). On multivariate analysis, young age, close resection margin, and triple-negativity were independent predictors of shorter RFS. Conclusion TN breast cancer had higher relapse rate and more aggressive clinicopathologic characteristics than non-TN in node-negative breast cancer. Thus, TN breast cancer should be integrated into the risk factor analysis for node-negative breast cancer.